Vulnerable children's health as described in investigations of reported children. Issue 2 (7th December 2011) - Hultman, Elin; Alm, Charlotte; Cederborg, Ann‐Christin; Fälth Magnusson, Karin
ABSTRACT: This study explores whether the social services weigh in health aspects, and what these may be, when investigating reported children's life situation. Information about physical and psychological health aspects for 259 children in 272 investigations was included. Overall, information about children's health was limited. Problematic emotions were the most commonly reported health aspect in the investigations, whereas suicidal thoughts, self‐harm behaviour and gastrointestinal and renal diseases were mentioned least of all. A cluster analysis revealed that the low level of health information group included the largest sample of data and consisted of investigations with minimal information about children's health. The three other cluster groups, Neurological diseases and psychosomatic symptoms, Emotional health and Physical and psychological health and destructive behaviour, consisted of investigations conducted mostly according to the model called Children's Needs In Focus (BBIC, in Swedish, Barns Behov i Centrum). Although these investigations also produced limited information, they provided more than those assessed as having a low level of information about health aspects. The conclusion is that it is necessary to increase information about health aspects in investigations if social welfare systems are to be able to fulfil their ambition of supporting vulnerable children's need of health care.